IMPLEMENTASI PAJAK PENGHASILAN BADAN PADA PT. BPR PURIDANA ARTHAMAS - Firmansyah, Rachmad; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the implementation of corporate income tax on PT. BPR Puridana Arthamas Sidoarjo and to find out the implementation of corporate income tax based on the taxing regulation. The research method is qualitative method which is done by using the descriptive analysis. The result of this research shows that PT. BPR Puridana Arthamas has prepared the financial statement of the company based on the prevailing Financial Accounting Standard. Due to the enforcement of the tax regulation then it generates commercial profit and statement and fiscal profit and loss statement. The influence of the implementation of the fiscal correction on PT. BPR Puridana Arthamas has made the fiscal profit and loss statement is larger than the commercial profit and loss statement and it has led income tax to underpayment. The company should follow the development of the tax regulation so obstacles in calculating the payable income tax.Keywords: Corporate Income Tax, Commercial Profit, Fiscal Profit.